Pendidikan Nilai Pada Anak Usia Dini di Kelompok Bermain dan Taman Kanak-Kanak Islam Terpadu - Setiawati, Suzzanna; Arifin, Zainal; Setiawati, Suzzana (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2015)
This study is based on the phenomenon of globalization, one of which had a negative impact on the values of life. Another impact of globalization is the emancipation of women who want a career. Busyness of parents who spend a lot of time resulting in early childhood education is not running with the maximum. This study is a qualitative research took place in KB and TK IT Karima Aqila Sinduadi, Sleman, Yogyakarta. data collection by observation, in-depth interviews and documentation. The results showed: (1) the value of education held in KB and TK IT Karima Aqila are: (a) the value of religious education, (b) Education of moral values, (c) social values education. (2) The methods used include: exemplary, habituation, advice, telling stories, singing, practices, supervision, communicate to parents, a tangle of love, punishment, providing initial information to children, play.